Effect of Perceived Organizational Support and Organizational Justice on Nurses’ Work Engagement with Intermediate Factors of Organizational Trust - Indra Theodorus; Wahyuni Dian Purwati; Mohamad Reza Hilmy (JMMR (Jurnal Medicoeticolegal dan Manajemen Rumah Sakit), 2021)
Work engagement is major concern for human resource management at XYZ Hospital Tangerang in order to improve performance of nursing profession. This study aims to study the effect of perceived organizational support and organizational justice on work engagement with intermediary factors of organizational trust. Quantitative associative research was conducted on 96 nurses in the hospital. XYZ Tangerang in March 2021, with primary data obtained by survey. The research instruments used are Utrecht Work Engagement Scale (UWES), The Survey of Perceived Organizational Support (SPOS), Measures of Trust, Trustworthines, and Performance Appraisal Perceptions, and Organizational Justice Survey. The data analysis method used is Path Analysis. The results of this study found that there was a significant positive effect of perceived organizational support on work engagement through organizational trust as an intermediary factor and a significant positive effect of organizational justice on work engagement through organizational trust as an intermediary factor, as well as a positive influence of organizational trust on work engagement. It was also found that the positive effect of perceived organizational support and organizational justice on organizational trust was found. Thus increasing organizational trust, perceived organizational support, and organizational justice will increase nursing work engagement.